Nanomateriais organofuncionalizados e suas aplicações em catálise: associando as vantagens da catálise homogênea com as da heterogênea - Inforzato, Tatiane (Universidade Federal de São Carlos, 2013)
We have immobilized proline, like prolinamide, by using flash chromatography with commercial grade silica and magnetite nanoparticles that were synthesized in our lab. The degree of functionalization has been determined by the nitrogen content from the data collected from elemental analysis of the particles. The organofunctionalization of the silica surface and the structure have been confirmed by 13C CP-TOS NMR and 29Si-NMR CPMAS solid state analysis. The confirmation of the catalyst-supported structure on functionalized magnetite can be correlated to the data obtained from the silica, since methodology was the same. The materials Pro-SiO2 and Fe3O4 @ SiO2-Pro were used in catalysis for the Michael reaction. The catalysts have been tested in several conditions: solvents, additive, reaction time and determined the minimum amount of catalyst needed to optimize reaction conditions. It was observed that the catalysis is best conducted without a solvent or in saturated NaCl solution and in the presence of additive, such as benzoic acid or acetic acid. The recyclability for both materials was satisfactory and no significant losses were observed after five cycles. The best results were obtained for propanone and cyclohexanone as a Michael donor and nitrostyrene as a Michael receptor with excellent yields and diastereoselectivity (in the case of cyclohexanone). Enantiomeric excess obtained for these reactions were too low to be observed proving the structural efficiency of the catalytic process.
Nanomaterials organofunctionalized and their applications in catalysis: the advantages of a member with the homogeneous catalysis heterogeneous
Keywords: Catálise; Materiais híbridos; Prolina; Michael, Reação de; Magnetita; CIENCIAS EXATAS E DA TERRA::QUIMICA